AL-LUGHAH AL-‘ARABIYYAH WA WADZAIFUHA WA KHASHAISHUHA WA DAURUHA FI AT-TARBIYYAH AS-SYAKHSYIYYAH - Khalid Yahya Abdurrahman Mahdaly; Aan Hasanah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
The Arabic language is one of the academic subjects that students learn in Islamic institutes and schools, and it is an important subject in them, because students do not communicate with them only, nor to obtain academic linguistic information and knowledge that students learn about the language only, but it increases their religious knowledge and it is one of the means of personal education. It is one of the world's languages ​​that has the social development of society and science. This article aims to answer the following questions: What is the concept of personal education and what are its characteristics? What is the concept of language and what are its functions? What is the relationship between education and linguistics? What is the role of the language teacher in education? The researcher followed the descriptive and analytical method, adopting the library research method. The most important results of the research is that the relationship of education with linguistics is a reciprocal relationship (influence each other), and linguistics and its fields and its teaching should be used in the interest in educating and building the personality. Language has an important role in our life and this necessitates the reality of awareness of this thing, especially for language teachers, so teaching is not a process of communicating information. Not only, but it is a means of disseminating educational values ​​and principles beneficial to the individual and society.